An ethnographic study on child laborers in Brgy. Simon Ledesma and Brgy. San Roque, Jaro, Iloilo City. - Lebanan, Jan Raoul F.
This study seeks to ethnographically describe the life and work of the child laborers to work. Interview and observation of respondents are the methods used in gathering data., The life of the child laborers in brgy. Simon Ledesma and brgy. San Roque is summarized as children coming from a big family whose parents' income is not enough in the family, and are living in the depressed areas of the barangays. The parents (as well as their children) did not able to reached higher level of education, thus obtained poorly paid and not stable jobs. The work of the child laborers are mainly street works, domestic works and industrial works and their income have three basis: monthly, daily and by piece. The primary factor that influenced these children to work is in the part of the parents who are unemployed or do not have a fixed income, and this factor resulted to several factors such as the child is not studying and the child wanted to help his/her parents in accommodating their daily needs. These children are identified through their work which had been influenced by the economic incapability of their parents, and this factor is identified from the life of the child laborers.